GE_GERICHTE PS/41/2018 vom 6. November 2018 - GE Cour de justice (2018)
RÉCUSATION ; PROCÉDURE PRÉPARATOIRE ; MAGISTRAT ; CONDUITE DU PROCÈS ; DOSSIER ; TRANSACTION(ACCORD) ; DESTRUCTION | CPP.56; CPP.59